Surface photovoltage property of magnesium ferrite/hematite heterostructured hollow nanospheres prepared with one-pot strategy - Shen, Y.; Zhao, Q.; Li, Xin Yong; Hou, Y.; Chen, G. (2012)
Magnesium ferrite/hematite heterostructured hollow nanospheres were successfully fabricated via a facile solvothermal method. The products were well characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, high resolution transmission electron microscopy, Fourier transform infrared spectroscopy, UV-vis absorption spectroscopy and surface photovoltage spectroscopy. From the absorption edge in the UV-vis absorption spectrum of MgFe 2O 4/a-Fe 2O 3 hollow nanospheres, an optical band-gap energy of about 1.986eV was estimated. Furthermore, it was observed that the heterostructured hollow nanospheres presented a remarkable surface photovoltage response in UV and visible spectral region, which was attributed to the effective formation of chemical interface between the two crystalline phases of MgFe 2O 4 and a-Fe 2O 3. © 2012 Elsevier B.V.